Modified logistic differential equation of neutral type with time delay - Donatas Švitra (Lietuvos Matematikos Rinkinys)
The following differential equation is considered: N(t) = rN[1 + a(1 − {N(t)}/K) − {N(t − h) + ρN(t − h)}/K]. The stable periodic solution based on the bifurcation theory of that differential equation is constructed.